EARTHQUAKERESISTANTSTRUCTURE - Sulemani, MdYamin; Alam, Maroof; Zama, MdRizwanul; Sultan, Md (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Earthquakes are serious problem as they affect life in hazardous manners. The Earthquake are mainly prevented by two methods namely Base Isolation Methods and Seismic Dampers. This report deals with Base Isolation and Seismic Dampers Methods in brief manner. Inertia is the reason for any building’s displacement in the direction opposite to that of ground’s motion. Baseisolated buildings undergo four times less acceleration as compared to fixed-base buildings. Reducing the vibrations in the structure is anotherwayofresistingdamage.Thisiswheredamperscomeintoplay.